2021
DOI: 10.1016/j.cmi.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of patients following hospitalization for coronavirus disease 2019: a prospective observational study

Abstract: Objectives: Few data are available regarding follow up of patients with coronavirus disease 2019 (COVID-19) after their discharge. We aim to describe the long-term outcomes of survivors of hospitalization for COVID-19 followed up first at an outpatient facility and subsequently by telephone. Methods: Observational prospective study conducted at a tertiary general hospital. Clinical and radiological progression was assessed and data were recorded on a standardized reporting form. Patients were divided into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 19 publications
3
25
0
6
Order By: Relevance
“…Among the 354 patients included in our cohort study, 36% of patients reported the presence of one or more symptoms after at least 9 months (in the mean) after COVID-19 onset. The most common symptoms were fatigue, dyspnea, and pain symptoms, which is consistent with the literature thus far [ 1 , 2 , 3 , 4 , 11 , 12 , 16 ]. These findings suggested systemic chronic inflammation with abnormal pro-inflammatory cytokine expression, which was observed in patients following COVID-19 [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among the 354 patients included in our cohort study, 36% of patients reported the presence of one or more symptoms after at least 9 months (in the mean) after COVID-19 onset. The most common symptoms were fatigue, dyspnea, and pain symptoms, which is consistent with the literature thus far [ 1 , 2 , 3 , 4 , 11 , 12 , 16 ]. These findings suggested systemic chronic inflammation with abnormal pro-inflammatory cytokine expression, which was observed in patients following COVID-19 [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the manual search of gray literature and preprints, 18 potentially related papers were included. After reviewing the titles and abstracts of the articles, 157 peer-reviewed papers or preprinted manuscripts were reviewed and a total of 91 articles were entered into the present meta-analysis [ 8 , [14] , [15] , [16] , [17] , [18] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ,…”
Section: Resultsmentioning
confidence: 99%
“…Although multiple recent studies have reported the long-term outcomes of COVID-19 survivors in the American [ 15 ], Asian [ 14 ] and European [ 4 , 16 18 ] settings, very few have examined the predictors of PACS. In the largest post-acute COVID-19 study to date conducted in the Veteran Affairs hospitals in the US and involving 73,435 non-hospitalized COVID-19 survivors beyond the first 30 days of illness, people with COVID-19 were found to be at higher risk of death and health care resource utilization, and to exhibit a broad array of incident pulmonary and extrapulmonary clinical manifestations within 6 months after diagnosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%